Experimental study on a novel bubble generator - Liu, Siyi (2016)
People pay lot of attentions to save energy in recent years due to the energy tight and environment protection. In ship production, the resistance reduction (drag reduction) is an important way to reduce energy consumption and fuel costs of ship. There are many frictional ways, including hull structure optimization, air lubrication and so on. In this dissertation, we focus on the air bubble drag reduction which is an application of air lubrication. Air bubble drag reduction is an extra device that generates air bubbles on the outside of the ship hull to reduce the density of fluid. This device reduces the wetted surface and breaks the boundary layer at ship hull in order to reduce the frictional resistance. A Japanese innovative device will be studied in this dissertation. It can generate air bubble without consuming any extra energy. The device is called the Winged Air Induction Pipe (WAIP), and it is based on the simple aerospace dynamics to generate air bubble when ship sails. An important part in this device is the hydrofoil that can generate a low pressure region above the wing when fluid flows to pass it. Air inlet is over the hydrofoil, such that the low pressure region can cause disturbances between the interfaces of air and water. It injects air into water, then generates air bubbles. In order to study the effect of WAIP further, we conduct experiments to study the ability of its air bubble generation in low fluid speed and how the parameters influence air bubble generation. In this dissertation, there are four major parameters we are going to study, which include the water velocity, air pressure at air inlet, air inlet angle, and attack angle of wing. Based on the experiment results and observation, several important conclusions are drawn below. ♦ Higher water velocity can improve air bubble generation. ♦ The higher air pressure can increase the number of air bubbles, but the number would be reduced because air bubbles would transform into air film if the air pressure is higher than the end pressure. ♦ High attack angle can enhance the ability of air bubble generation. ♦ Regarding the influence of air inlet angle that may be negative or positive, when the angle is negative, the air bubble generation is restrained with the angle reducing (from 0° to -50°). When this angle is positive, the air bubble generation is restrained firstly and then promoted.